Sludge reduction using aquatic worms under different aeration regimes. Issue 6 (19th March 2017) - Cai, Lu; Gao, Ding; Wang, Kan; Liu, Hong-tao; Wan, Xiao-ming
ABSTRACT: Adding aquatic worms to a wastewater treatment system can reduce sludge production through predation. The aeration level is crucial for success. To evaluate aeration impacts on sludge reduction and determine an optimal aeration regime, this study investigated the processes of in-situ sludge reduction, using aquatic worms exposed to different aeration levels. The experiment also compared treatment results between a conventional reactor and an aquatic worm reactor (WR). Results indicated that the recommended concentration of dissolved oxygen (DO) was 2.5 mg L −1 . The removal rate of chemical oxygen demand remained steady at 80% when the DO concentration was higher than 2.5 mg L −1, while the removal rate of ammonia nitrogen continued to moderately increase. Increasing the DO concentration to 5 mg L −1 did not improve sludge reduction, and consumed more power. With a DO concentration of 2.5 mg L −1 and a power of 0.19 kWh t −1 water, the absolute sludge reduction and relative sludge reduction rates in the WR were 60.0% and 45.7%, respectively, and the daily aquatic worm growth rate was 0.150 d −1 during the 17-d test. Therefore, at the recommended aeration regime, aquatic worms reduced the sludge without increasing the power consumption or deteriorating the effluent.